The Influence of Organizational Culture, Cognitive Abilities, Work Team On The Performance of Private University Lecturer In Kopertais Region IX, North Sumatra - Andriani, Rini Dewi; Lubis, Saiful Akhyar; Wijaya, Candra (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research is to find out; 1) direct influence of organizational culture on lecturer performance, 2) direct influence of lecturer cognitive abilities on lecturer performance, 3) direct influence of lecturer work teams on lecturer performance, 4) influence of organizational culture on work teams, 5) direct influence of cognitive abilities on work teams , 6) the indirect influence of organizational culture on performance through work teams, 7) the indirect influence of cognitive abilities on lecturer performance through work teams. This research uses quantitative methods, with a form of descriptive research that processes data using the results of distributing questionnaires to population samples, so as to obtain a significant relationship and a mutual tendency towards the probability of error regarding the hypothesis being built. This type of research approaches path analysis (path analysis). This research examines or analyzes the relationship between research variables, as well as measuring the influence of one variable on other variables. In this research, there are four variables that will be studied, namely (1) organizational culture, (2) cognitive abilities, (3) work team, and (4) lecturer performance. The population in this study were all permanent lecturers at private universities consisting of forty-three (43) universities and high schools in Kopertais Region IX, North Sumatra. The sample used in this research was proportional random sampling guided by the Krejcle and Morgan tables. The research sample included 311 lecturers from eight (8) universities and high schools in Kopertais Region IX, North Sumatra who were still active until 2021/2022. The results of the research, the R-Square value of Lecturer Performance (Y) is 0.760, which means that Organizational Culture (X1), Cognitive Ability (X2), and Work Team (X3) are able to explain Lecturer Performance (Y) by 76%, the remaining 24% explained by other factors, the R-Square value of the Work Team (X3) is 0.500, which means that Organizational Culture (X1) and Cognitive Ability (X2) are able to explain the Work Team (X3) by 50%, the remaining 50% is explained by other factors, Organizational Culture (X1) has a positive and significant effect on Lecturer Performance (Y), with a coefficient value (Original Sample column) = 0.383, and P-Values = 0.000 < 0.05 (Hypothesis Accepted),